Model Systems to Study Plague Pathogenesis and Develop New Therapeutics - Lawrenz, Matthew B. (Frontiers in Microbiology, 2010)
The Gram negative bacterium Yersinia pestis can infect humans by multiple routes to cause plague. Three plague pandemics have occurred and Y. pestis has been linked to biowarfare in the past. The continued risk of plague as a bioweapon has prompted increased research to understand Y. pestis pathogenesis and develop new plague therapeutics. Several in vivo models have been developed for this research and are reviewed here.